Health Promotion Using the Lecture Method Effective in Preventing Bullying Behavior Among Junior High School Students - Yanti, Putri; Allo, Asna Ampang (Jurnal Ilmiah Kesehatan (JIKA), 2025)
Bullying is a serious issue affecting adolescents globally, particularly those aged 13-15. It significantly contributes to mental health problems and increases the risk of suicide. However, bullying often goes unaddressed due to its subtle impact and underreporting by victims. Therefore, practical strategies are needed to encourage student involvement in preventing bullying. This study evaluated the effectiveness of using lectures with audiovisual media to prevent bullying among junior high school students in Makassar. A quasi-experimental design was used with a pretest-posttest and control group. The study involved 100 students divided into an intervention group (SMP Negeri 1 Makassar) and a control group (SMP Negeri 6 Makassar). Knowledge and attitude were assessed using questionnaires. Data analysis included frequency distribution and bivariate analysis using Mann-Whitney and Wilcoxon tests. Results showed a significant difference in knowledge scores between groups (p-value=0,027) and a significant improvement in attitudes toward bullying prevention (p-value=0,001). The study concludes that health promotion using lectures and audiovisual media effectively improves student knowledge and attitudes toward bullying prevention. It is recommended that schools conduct regular health promotion activities addressing social issues such as bullying.